Simbol-simbol Pada Drama yang Berjudul “It’s Okay To Not Be Okay” - Ari Fajria Novari (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2020)
The writer of literature work sometimes takes the idea and way of thinking from her dynamic society. Those dynamic sometimes consist of certain symbol. The one of ways to reveal the symbol is by using semiotic structural approach. This study has aim to analyze symbols which are found in drama with the title “It’s Okay to not be Okay”. The method applied is descriptive. The result shows that there are elevent symbols in the story. The general meaning in symbol is about the moral, ethics, parenting and characters of style. One of them is the action of the characters of style Moon Sang Tae (the brother of Moon Kang Tae) he is an sindrom autism people because he usually wearing the lines t-shirt everyday. The action is the symbol of moral, ethics, parenting and characters of style can not be maintained only through appeal and advice, but there should be give the examples and theories. And the purposes from the writer drama is to give massages for the parents, children and the societies.